Canadian and U.S. adjustment policies in a bilateral trade agreement - Wonnacott, Ronald J.; Hill, Roderick; Canadian-American Committee (Toronto, Ontario; Washington, D.C. : Canadian-American Committee, 1987)
This study examines the Canada-U.S. free trade agreement as well as various means that U.S and Canada governments have employed to assist workers adversely affected by trade liberalization.
"Sponsored by C.D. Howe Institute (Canada) [and] National Planning Association (U.S.A.)."
"September 1987"--T.p. verso.
Includes bibliographical references (p. 130-136).
osa 24/1/19
Loans
Keywords: Trade adjustment assistance; Foreign trade and employment; Canada; United States